Association of vascular invasion with increased mortality in patients with minimally invasive follicular thyroid carcinoma but not widely invasive follicular thyroid carcinoma. Issue 12 (27th February 2014) - Kim, Hye Jeong; Sung, Ji‐Youn; Oh, Young Lyun; Kim, Jung Han; Son, Young‐Ik; Min, Yong‐Ki; Kim, Sun Wook; Chung, Jae Hoon
Abstract Background The association of vascular invasion with tumor aggressiveness and poor prognosis in follicular thyroid carcinoma (FTC) remains controversial. Methods We reviewed medical records of 204 patients with histologically confirmed FTC. Results The disease‐specific survival rates at 5 and 10 years were 94% and 85%, respectively. Using Cox proportional hazard model, the extent of invasiveness and the frequency of distant metastasis were found to be independent prognostic factors for survival in all patients with FTC. When we performed individual analyses stratified by the extent of invasiveness, vascular invasion was an independent predictor of disease‐specific survival in minimally invasive FTC, but that did not independently affect survival in widely invasive FTC. Conclusion This study suggests that vascular invasion is associated with aggressive features of FTC and independently influences outcomes in minimally invasive FTC. For patients aged <45 years with minimally invasive FTC without vascular invasion, thyroid lobectomy alone may be adequate. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1695–1700, 2014